The Complexity of FGF23 Effects on Cardiomyocytes in Normal and Uremic Milieu - Andreja Figurek; Merita Rroji; Goce Spasovski (Cells, 2021)
Fibroblast growth factor-23 (FGF23) appears to be one of the most promising biomarkers and predictors of cardiovascular risk in patients with heart disease and normal kidney function, but moreover in those with chronic kidney disease (CKD). This review summarizes the current knowledge of FGF23 mechanisms of action in the myocardium in the physiological and pathophysiological state of CKD, as well as its cross-talk to other important signaling pathways in cardiomyocytes. In this regard, current therapeutic possibilities and future perspectives are also discussed.